EXPLORING THE THERAPEUTIC POTENTIAL OF CATHARANTHUS ROSEUS: UNVEILING ITS DIVERSE PHYTOCHEMICALS AND MECHANISMS OF ACTION FOR CHRONIC AND INFECTIOUS DISEASES - MALHOTRA, MEENAKSHI; RANA, HIMANI; TANDON, SHUBHAM (International Journal of Current Pharmaceutical Research, 2024)
Medicinal plants have long been recognized for their potential in traditional medicine, offering a rich repository of phytochemicals with diverse therapeutic properties. These natural remedies often present fewer side effects when compared to synthetic agents, making them an attractive alternative. Among these botanical treasures, Catharanthus roseus (commonly known as c. roseus) has garnered significant attention due to its wide array of phytochemicals boasting various biological activities, such as antioxidant, antibacterial, antifungal, antidiabetic, and anticancer properties. C. roseus, known colloquially as Vinca rosea, has a storied history of application in treating various ailments across numerous countries. Notably, it has contributed ground-breaking compounds to clinical medicine, with vinblastine and vincristine being the first therapeutics derived from this plant. Furthermore, compounds like vindoline, vindolidine, vindolicine, and vindolinine found in the leaves of C. roseus exhibit potent antidiabetic effects. The ongoing research in recent years has unearthed novel insights that reshape our understanding of the mechanisms underlying the therapeutic potential of Vinca rosea. This burgeoning knowledge amplifies the prospects of this plant as a valuable source of bioactive substances for a wide range of therapeutic applications.